Utilização de corrente microgalvânica para o desenvolvimento de dois protocolos para tratamento de estrias albas - Costa, Cristiane Ferreira da (2016)
The development of stretch marks during pregnancy is considered the most common physiological change of connective tissue and there are few alternative treatments designed to soften the appearance of this change. This study developed and applied two protocols for the treatment of striae alba arising during pregnancy using microgalvanic current and checking its effects. This was an exploratory study, experimental, quantitative and qualitative approach, consisting of 26 volunteers aged between 20 and 35 years also divided into two groups. It began the study after signing the Statement of Consent. Both groups received 15 treatment sessions with the microgalvanic current modulated 100μA (microamps) being a session every 12 days apart. Group A received the treatment with the longitudinal puncturing technique and the B group received the cross puncturing technique. All participants answered a questionnaire on the intensity of pain, type of pain and satisfaction with treatment, and underwent physical therapy evaluation at the beginning, after the fifth, tenth and fifteenth session of the proposed treatment protocol. All streaks were treated, however, three streaks of each volunteer was selected to be monitored being shot and having its area, length and width analyzed using the ImageJ software, manual planimetry and pachymetry. The five sessions was a comparison of the results within each group and between groups in order to assess what is the best protocol and wherein the required amount of sessions to approximate the appearance of the striae chosen to be normal skin. Group A showed significant differences after five treatment sessions while the B group needed 15 sessions to present results similar to group A in reducing the size of stretch marks. However, the two applicable protocols were effective in reducing the size of striae. In the comparison between groups for pain intensity was found statistically significant (p = 0.000) for group A which showed greater pain than in group B. With regard to women's satisfaction with the treatment, there was no statistically significant difference between groups. In group A, 38.4% of voluntary reported great satisfaction, 53.8% and 7.7% satisfaction little satisfaction with treatment. The B group reported 38.4% of great satisfaction, 46.5% and 15.4% satisfaction low satisfaction with treatment.